PERENCANAAN KARIER SISWA SMA NEGERI 1 NGLAMES KABUPATEN MADIUN - Silvia Yula Wardani; Rischa Pramudia Trisnani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This research was conducted at SMA Negeri 1 Nglames, Madiun Regency with a quantitative descriptive design. Purposive this research to describe the career planning of students of SMA Negeri 1 Nglames Kabupaten Madiun. In this study focused on the level of student career planning. The research instrument used is a student career planning scale. The results of the discussion, show that student career planning is still very low. Student career planning is still low, seen from low self-understanding, low self-confidence, lack of information on lanut studies and types of work that are in line with their potential. This happens because guidance and counseling services are not carried out classically or counseling and guidance services are not included in class hours for students in class X and XI. Classical guidance and counseling services are only given to class XII students only. It is recommended that teachers improve their understanding of career planning, act more responsively when there are students who need career information and schools need to have a preventive program that involves all the components involved in the process of improving student career planning.Keywords: career planning